A new discrete element model for rock-like materials. (1st April 2022) - Zhao, Haiyang; Zhang, Liangchi; Wu, Zhonghuai; Liu, Ang
Highlights: The new DEM model is of high computational efficiency and stress predictability. The new DEM model has superior advantages in revealing crack nucleation and propagation. Cracking details can be accurately revealed. Material failure can be reliably predicted. Abstract: Rock-like materials such as sandstone, concrete and ceramic are composed of cemented discrete particles. As such, the discrete element method can effectively characterize the fracturing behaviour of those materials. This paper presents a new discrete element model for rock-like materials. The model is superior to most discrete element-based models in algorithm simplicity since a simple translational movement of particles and a simple tensile yield criterion defined in the model are sufficient to capture the behaviours of a rock-like material. Thus, the rotation and torque calculations can be safely removed from the algorithm. In addition, the model has advantage over most discrete element models in stress analysis, and the stress distribution predicted by the proposed model agrees very well with both the analytical and finite element solutions. Besides, the crack patterns predicted by the model agree well with the experimental observations. Therefore, the model is more effective in predicting crack nucleation, growth and propagation of rock-like materials.